PCSK9 is Present in Human Cerebrospinal Fluid and is Maintained at Remarkably Constant Concentrations Throughout the Course of the Day. Issue 5 (25th March 2014) - Chen, Yan Q.; Troutt, Jason S.; Konrad, Robert J.
Abstract: Proprotein convertase subtilisin kexin type 9 (PCSK9) is a key regulator of serum low density lipoprotein cholesterol levels. PCSK9 is secreted by the liver and binds the hepatic low density lipoprotein receptor, causing its subsequent degradation. PCSK9 has also been shown to regulate the levels of additional membrane‐bound proteins in vitro, including very low‐density lipoprotein receptor, apolipoprotein E receptor 2, and beta‐site amyloid precursor protein‐cleaving enzyme 1, which are highly expressed in central nervous system (CNS) and have been implicated in Alzheimer's disease. Previous studies have demonstrated that human circulating PCSK9 displays a diurnal rhythm. Currently, little is known about PCSK9 levels in human cerebrospinal fluid (CSF). In the present study, we measured PCSK9 concentrations in both serum and CSF collected from healthy human subjects at multiple time points throughout the day. While PCSK9 in serum manifested a distinct diurnal pattern, CSF PCSK9 levels were remarkably constant throughout the course of the day and were also consistently lower than corresponding serum PCSK9 concentrations. Our results indicate that regulation of PCSK9 in human CSF may be different than for plasma PCSK9, suggesting that further study of the role of PCSK9 in the CNS is warranted.